2021
DOI: 10.5194/tc-15-3279-2021
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical constraints on the properties of a subglacial lake in northwest Greenland

Abstract: Abstract. In this study, we report the results of an active-source seismology and ground-penetrating radar survey performed in northwestern Greenland at a site where the presence of a subglacial lake beneath the accumulation area has previously been proposed. Both seismic and radar results show a flat reflector approximately 830–845 m below the surface, with a seismic reflection coefficient of −0.43 ± 0.17, which is consistent with the acoustic impedance contrast between a layer of water and glacial ice. Addit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…(2013), and further characterized by Maguire et al. (2021), who estimate the depth of the lake at 10–15 m. This site falls within the Mesoproterozoic Thule basin terrane and Inglefield mobile belt of northwestern Greenland (Dawes, 2009). Only 14 events above M w 5.0 occurred during the deployment, with no events larger than a M w 5.9.…”
Section: Icy Ocean World Geophysical Analog Site and Data Collectionmentioning
confidence: 74%
See 1 more Smart Citation
“…(2013), and further characterized by Maguire et al. (2021), who estimate the depth of the lake at 10–15 m. This site falls within the Mesoproterozoic Thule basin terrane and Inglefield mobile belt of northwestern Greenland (Dawes, 2009). Only 14 events above M w 5.0 occurred during the deployment, with no events larger than a M w 5.9.…”
Section: Icy Ocean World Geophysical Analog Site and Data Collectionmentioning
confidence: 74%
“…The Greenland location was also colder (−14°C to −2°C) than the Alaska site and in the accumulation area, which reduces surface activity such as melt runoff and moulins significantly, producing quieter power density function (Figure 1c). The northwest Greenland stations were situated near the ice divide with an ice thickness of ∼850 m (Maguire et al., 2021), of this thickness, the top 45 m is firn. The site is situated over a subglacial lake first identified by Palmer et al.…”
Section: Icy Ocean World Geophysical Analog Site and Data Collectionmentioning
confidence: 99%
“…Several process-level studies of potential heat sources have been performed, which compare individual observed temperature profiles from local areas with temperature profiles modeled by a thermal, or themo-mechanical, ice flow model (Iken et al, 1993;Lüthi et al, 2002;Harrington et al, 2015;Lüthi et al, 2015;Meierbachtol et al, 2015;McDowell et al, 2021;Law et al, 2021;Maguire et al, 2021). Although these studies featured different local areas, the comparisons generally showed that models tend to underestimate englacial temperatures, and thus need to incorporate additional heat sources in order to reproduce observed ice temperature profiles.…”
Section: Sources Of Uncertaintymentioning
confidence: 99%
“…The changes in temperature reduce the seismic quality factor (increasing attenuation) (Cammarano et al., 2006). For these reasons, seismic waves traveling in a thinner ice shell will likely have stronger ground motion at lower frequencies compared to a thicker ice shell (Maguire et al., 2021; Panning et al., 2018). It is worth noting that the ground motion will be dependent on frequency content, such that if surface waves have wavelengths greater than the thickness of the ice, the resulting ground motion will be drastically reduced due to interactions with the ocean.…”
Section: Introductionmentioning
confidence: 99%